2022
DOI: 10.3389/fpain.2022.839463
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Neuromodulation for Treatment of Drug-Resistant Epilepsy

Abstract: Epilepsy is a neurological disorder that affects more than 70 million people globally. A considerable proportion of epilepsy is resistant to anti-epileptic drugs (AED). For patients with drug-resistant epilepsy (DRE), who are not eligible for resective or ablative surgery, neuromodulation has been a palliative option. Since the approval of vagus nerve stimulation (VNS) in 1997, expansion to include other modalities, such as deep brain stimulation (DBS) and responsive neurostimulation (RNS), has led to improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Neuromodulation and neurostimulation can also include the use of non-invasive techniques, such as transcranial magnetic stimulation or transcranial direct-current stimulation, that can modulate cortical excitability or plasticity [300,301]. For example, a study using precision medicine for the diagnosis and treatment of viral infections and epilepsy suggested that neuromodulation and neurostimulation may be useful for patients with refractory epilepsy who are not candidates for surgery or who have contraindications to antiviral drugs or anticonvulsant drugs [302].…”
Section: Future Directions and Precision Therapiesmentioning
confidence: 99%
“…Neuromodulation and neurostimulation can also include the use of non-invasive techniques, such as transcranial magnetic stimulation or transcranial direct-current stimulation, that can modulate cortical excitability or plasticity [300,301]. For example, a study using precision medicine for the diagnosis and treatment of viral infections and epilepsy suggested that neuromodulation and neurostimulation may be useful for patients with refractory epilepsy who are not candidates for surgery or who have contraindications to antiviral drugs or anticonvulsant drugs [302].…”
Section: Future Directions and Precision Therapiesmentioning
confidence: 99%
“…Neuromodulation therapy acts as a non-pharmacological treatment for epilepsy; this type of therapy directly stimulates or prevents the conduction of electrical potential in the brain [139]. Neuromodulation acts directly on the electrical conduction system of the CNS, modulating or modifying brain excitability and impacting the intensity and frequency of seizures in cases of epilepsy [140,141].…”
Section: Neuromodulation Therapymentioning
confidence: 99%
“…This method is also a non-invasive technique that helps in epilepsy treatment by anticipating tonic-clonic and generalized seizures [139]. The mechanism of TNS is a similar to that of VNS, where the trigeminal nerve is part of the nucleus of the solitary tract (NTS) and locus coeruleus (LC), brain regions that are involved in seizure reduction [139,140,157,164].…”
Section: Trigeminal Nerve Stimulationmentioning
confidence: 99%
“…Novel VNS approaches, such as non-invasive vagus nerve stimulation (nVNS), are being studied to explore their effectiveness as a less invasive alternative to traditional VNS therapy [ 90 , 91 ]. Some studies are investigating the potential synergistic effects of combining VNS with other neuromodulation techniques or with specific ASMs to enhance seizure control [ 92 , 93 , 94 ]. As VNS research continues to evolve, ongoing clinical trials hold the promise of further elucidating the therapeutic potential of VNS in various epilepsy syndromes and refining patient selection criteria for optimal outcomes.…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%